Research on the Coordinated Development and Optimization Path of Digital Economy and Green and Low-Carbon Consumption under the Double-Carbon Target : Take Anhui Province as an example - Nie, Yu; Li, Lixian; Huang, Xuehua; He, Tingting (International Journal of Global Economics and Management, 2024)
At present, China is in the stage of rapid development of the digital economy, which has a good foundation and great potential in infrastructure and talent construction, and the development prospect of the digital economy is very broad. But at the same time carbon emissions also need us to focus on, in the face of climate change for the urban natural ecosystem and economic system, digital economy how to reduce carbon emissions, not only can improve the city for climate change, can also for the government in the dual carbon target provide new policy advice and perspective, and for producers and consumers, can better regulate their behavior, promote the development of low carbon. The current situation of green economy development in Anhui Province combined with social practice research, Using the coupled development model to explore the relationship between green economy and green and low-carbon consumption, Based on the two-carbon background, Based on the survey of some areas of Anhui Province, By constructing an index system for the coupled development model, The coupling coordination between green economy and green low-carbon consumption by coupled development model, As such, the grey association method was used, To explore the other influencing factors, Then, analyze the coupling mechanism affecting the development of the two and put forward countermeasures and suggestions to promote the virtuous cycle of the coordinated development of digital economy and green consumption, It provides new ideas and methods for high quality development of urban economy and sustainable development.